Kontribusi Wanita Tani dalam Kegiatan Usahatani Kacang Tanah di Desa Kota Wuna Kecamatan Tongkuno Kabupaten Muna - Baso, Trisnawati; Batoa, Hartina; Limi, Muhammad Aswar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aimed to: (1) determine the contribution of women farmers in peanut farming activities, and (2) determine working hours of women farmers in peanut farming activities in the Kota Wuna village Tongkuno subdistrict Muna district. Population for this study includes all women farmers were farming peanuts in Kota Wuna village Tongkuno subdistrict Muna district. Simple random sampling was used to select 39 women farmers peanuts. Data were analyzed using the interval to determine the contribution of women farmers and HKP to know the working hours of women farmers. The results of this study were (1) The contribution of women farmers in peanut farming activities with high category include land clearing, planting techniques, maintenance, post-harvest, and marketing. The medium category includes harvest. The low category includes the installation of fencing and netting fence. and (2) Working hours of women farmers to farm peanuts in the Village District of Tongkuno Wuna City Muna is at 6.90 HKP land clearing, planting techniques amounted to 4.31 HKP, amounting to 2.84 HKP fencing, installation of fence nets 2.38 HKP, maintenance amounting to 5.81 HKP, amounting to 7.30 HKP harvest, post-harvest of 4.20 HKP, and marketing of 1.86 HKP.